Britain in Tudor Times - Macdonald, Fiona (London Franklin Watts, 2003)
A richly illustrated guide to life in Britain during Tudor times. The book uses as a starting point the sites and artefacts that have survived and use this evidence to build up a picture of everyday life at the time
Include Color Illustration, Glossary and Index
Keywords: Manners and customs -- Great Britain -- England